Improvement of low-cycle fatigue resistance in TWIP steel by regulating the grain size and distribution. (1st August 2017) - Shao, C.W.; Zhang, P.; Zhu, Y.K.; Zhang, Z.J.; Pang, J.C.; Zhang, Z.F.
Abstract: Compared to stress controlled high-cycle fatigue, enhancing strain controlled low-cycle fatigue (LCF) properties of material is much more difficult and less reported. In this study, we introduced two strategies and technologies to improve the LCF performance of Fe-Mn-C twinning induced plasticity (TWIP) steel. One is grain refining without introducing residual stress by traditional cold rolling and following recrystallization annealing (FG sample); the other is to introduce a linear gradient in grain size into TWIP steel by the original processing technology (GS sample). It is found that GS samples exhibit a higher cyclic hardening ability and cyclic saturation stress than that of as-received coarse grain (CG) samples and FG samples, which invalids the rule of mixture. Based on the dependence of the fatigue life ( N f ) on the total strain amplitude (Δε/2), GS shows the longest life at high strain amplitudes, while FG shows the longest life at low strain amplitudes. Judging from the aspect of stress (Δσ/2- N f curve), i.e. the Basquin curve, GS exhibits a better LCF performance than both FG and CG. The excellent fatigue properties of GS are believed to originate from the large generation of geometrically necessary dislocations (GNDs) and the formation of hard core and soft shell structure during cyclic loading. The significant influences of grain size and distribution on fatigue damage mechanisms may provide new and important implications for the optimized microstructural design of the high fatigue performance material. Graphical abstract: A gradient structure in grain size (GS) along the radial direction was introduced into twinning induced plasticity (TWIP) steel by the original torsion & annealing treatment. Comparing with the homogeneous coarse grain (CG) or fine grain (FG) material, GS shows a better low-cycle fatigue property, evading the rule of mixture.